Strata pressure behavior and overlying strata movement characteristics of slicing backfill mining in thick coal seams. Issue 3 (May 2023) - Li, Zhihua; Yang, Ke; Wei, Tingshuang; Liu, Cheng; Zhou, Peng; Miao, Jianhua
To improve the coal recovery rate, paste backfill mining was used for 3# coal seam under the industrial square in Panji No.4 Coal Mine. Theoretical analysis, numerical simulation, and similar simulation were applied to study the underground pressure behavior and the overlying strata movement. Results demonstrate the following. (a) Caving mining exerts IV-level mining-induced damages to ground buildings, while slicing backfill mining only causes I-level mining-induced damages to ground buildings. (b) The maximum surface subsidence coefficient of backfill mining is 0.02, and the maximum surface subsidence value is only 4.12% of that under caving mining. (c) The front abutment pressure peak of the working face in caving mining is 28.31 MPa and only 17.82 MPa in backfill mining, which is only 62.95% of caving mining. The distance from the stress peak to the coal wall decreases from 11.14 to 3.04 m. Therefore, the paste backfilling mining of 3# coal seam below the industrial square of Panji No. 4 Coal Mine can effectively control the overlying strata movement and decrease the surface subsidence significantly. Compared with caving mining, backfill mining significantly relieves the strata pressure behaviors and narrows the distance of mining influence.